Avaliação da aprendizagem em salas multisseriadas: educando o olhar - Silva, Antonia Mônica da (2024)
This paper is a master's research project from the Graduate Program in Education (PPGE) at the Federal University of Ceará (UFC), carried out in four public schools in the municipality of Campos Sales (CE), with the general objective of reflecting on the assessment practices of teachers in multi-seriate classes in elementary school in the municipality of Campos Sales (CE). The evaluation practices carried out in the multiserial classes in elementary school were identified; these evaluation practices were related to the conceptions of evaluation; and the impact of evaluation practices on the learning of students in the multiserial classes in the municipality was described. This research is a basic, qualitative, descriptive and content analysis study. With regard to the methodological approach, it was decided to carry out the research with teachers of Portuguese language subjects from the 1st to 3rd year of elementary school in four multi-grade public schools in the municipality of Campos Sales-CE, as the literacy stage is considered crucial for the development of predictive skills. In addition, it is justified that the evaluation is presented as a tool to help teachers reorganize their practice with a view to respecting the specificities of these classes and corroborating the quality of teaching and learning. The research was also divided into three parts in order to achieve the proposed objectives. In the first part, the main works by Luckesi (2011), Saul (2008), Hoffmann (2009) and Vasconcelos (2008) were used as a theoretical basis to reflect on the conceptions of educational assessment. Parente (2020) and Hage (2008) were used to discuss the issue of multigrade classes. Secondly, interviews were conducted with the teachers of the multigrade classrooms chosen and, finally, observations were made in order to relate the teachers' statements to classroom practices. The results showed important points about assessment practices in these classes, including the use of written tests as the main assessment tool; the need for specific training for these classes in order to help teachers carry out the assessment process and the need for public policies that take into account the specificities of multigrade classrooms. The conclusion is that the assessment practices developed in multigrade classrooms are still related to traditional assessment models and that there is a need for training on the subject in order to develop assessment practices that respect the specificities of this type of teaching.